DAMPAK PERTUMBUHAN EKONOMI DAN DANA ALOKASI UMUM TERHADAP TINGKAT KEMISKINAN DI PROVINSI ACEH - Husnul Khatimah; Ichsan Ichsan (Jurnal Ekonomi Regional Unimal, 2022)
This study examines the effect of economic growth and General Allocation Funds (DAU) on the poverty level in Aceh Province. This study used secondary data from 2015 to 2019 accessed on www.bps.go.id. The data analysis method used was panel data regression analysis. The results of partial tests show that economic growth has a negative and significant effect on the poverty level in Aceh Province, and DAU has a positive and significant effect. Simultaneously, economic growth and DAU has a positive and significant effect on the poverty level in Aceh Province.